The Book of Mormon and the Problem of the Pentateuch - Sperry, Sidney B. (Journal of Book of Mormon studies, 1995)
Many critics deny that the first five books of the Old Testament were written by Moses and consider them to be childish myths. However, when Nephi and Lehi examined the brass plates, they found them to contain "the five books of Moses." And in the Book of Mormon, the Savior himself confirms their authorship. The book of Ether also offers confirmation of the Tower of Babel story.